7 GLP-1 cardioprotection is not mitochondrial K-ATP channel dependent. (24th April 2016) - Giblett, JP; Axell, RJ; Clarke, SJ; McCormick, LM; Read, PA; Reinhold, J; O'Sullivan, M; West, NEJ; White, PA; Dutka, DP; Hoole, SP
Abstract : Introduction: Glucagon-like Peptide-1 (GLP-1) protects against left ventricular (LV) stunning but the mechanism is unclear. Two protocols (P1 and P2) investigated whether blockade of mitochondrial K-ATP channels (responsible for ischaemic conditioning) with glibenclamide abrogates GLP-1 cardioprotection in humans. Methods: P1. Patients attending for elective PCI to their LAD were assigned to 4 groups (Figure 1 ). Pressure-volume loops, allowing systolic/diastolic assessment, were recorded at baseline (BL1) and after 1-minute LAD balloon occlusion (BO1). GLP-1 or saline infusion was started after BO1, with loops repeated (BL2 and BO2) at 30mins. P2. Patients awaiting PCI underwent serial dobutamine stress echos (DSE) with tissue Doppler, to assess impact of GLP-1 and glibenclamide on global and regional systolic function. Results: P1. BO1 reduced LV function in all groups. Recovery from stunning (BL2) and cumulative dysfunction (BO2) improved with GLP-1 alone, and when glibenclamide was added. P2. At peak stress and recovery there was additional improvement in systolic function with GLP-1 versus control. However, systolic function was unchanged, with and without glibenclamide. Conclusion: Glibenclamide did not abrogate GLP-1-mediated cardioprotection, suggesting GLP-1 acts through a non-KATP-dependent pathway in humans.